“Nic dwa razy,” “nada dos veces,” “nothing twice”: An analysis of the translation of the poetry of Wisława Szymborska - Lechowska, Bożena; Uribe Salamanca, Edga Mireya (Rastros Rostros, 2016)
Aim: Communication between cultures is made possible through interpreters and translators, with written texts generating awareness of populations. That said, in literature, particularly in poetry, a paradigm of translatability and liberty arises. In order to illustrate this, we propose in the line of translation studies of theglot ta research group a semantic analysis of the Spanish and English versions of the poem “Nagrobek” by the recipient of the 1996 Nobel Prize in Literature and one of the most prominent figures in Polish poetry, Wisława Szymborska.  Description: The analysis in this article, based on a typology of reflection, shows that to translate is to go beyond the merely linguistic: our emphasis has as its center the meaning, the receiver/reader, and his or her possible reactions to three versions of translation. Point of view: The theoretical framework revolves around the approaches of dynamic and formal equivalence of Eugene Nida. Conclusions: The effect produced by a translation is not identical to the original, instead varying among the different languages of the versions put forward of the same text. We concluded that a work translated by several translators, although of the same original text, will never produce one single product. It is clear that translators of poetic texts must distance themselves from the original to take liberties andrecreate it, as in translation there must be “nothing twice.”
Keywords: literature; Polish poetry; translation; version; Wisława Szymborska